Maintenance of species integrity in the context of a recent radiation: the case of Jamesbrittenia (Scrophulariaceae: Limoselleae) in southern Africa. (12th August 2016) - Verboom, George Anthony; Herron, Margaret L.; Moncrieff, Glenn R.; Slingsby, Jasper A.
Abstract : Incomplete post‐zygotic isolation poses challenges for the maintenance of species integrity in recently radiated lineages. An example is Jamesbrittenia, a southern African‐centred genus, the species of which cross readily to produce viable offspring. We develop a dated phylogenetic hypothesis for Jamesbrittenia and used this to assess the evidence for recent radiation and to evaluate the roles of geography, relatedness and floral divergence in determining the incidence of wild hybridization. Phylogenetic inference is based on nuclear ( GScp ) and plastid ( rps16, psb–trnH ) loci, but uses morphological evidence to resolve instances of supported incongruence. Our data reveal four ecologically and biogeographically differentiated lineages in Jamesbrittenia . One of these, a widespread and predominantly shrubby lineage, reflects accelerated diversification, potentially triggered by environmental change, starting in the late Miocene epoch. In the widespread clade, strong range exclusivity indicates an important role for geography in maintaining species identity. Among species with overlapping ranges, however, differentiation in floral form is a powerful predictor of wild hybridization. The apparent importance of geography in maintaining species integrity in recently diverged lineages, like the widespread clade of Jamesbrittenia, needs to be considered when species are translocated, whether such translocation is horticulturally motivated or forms part of an 'assisted migration' exercise.